The Impact Of Fintech Growth On Banking In Indonesia - Muryani Arsal; Arif Awal; Cut Putri Ikhtiar Arta; Risky Amelia (CV. AFDIFAL MAJU BERKAH, 2025)
Fintech is a new technology that allows financial institutions to harness the potential of blockchain and improve the security and transparency of the financial services it provides. The aim of this research is to determine the impact of the growth of financial technology (FINTECH) on banking performance in Indonesia. A qualitative approach is used to understand the impact and role of fintech in banking development. The results of the analysis show that fintech has a positive and significant impact on the performance of banks listed on the Indonesia Stock Exchange. As a step forward, banking in Indonesia needs to continue to innovate, adapt to new technology, and strengthen regulations that support the fintech industry. Collaboration between the banking and fintech sectors, as well as improving security systems and data protection, will be key to maintaining the integrity and digital financial ecosystem.